Comparison of the efficacy of acupuncture-related Therapies for post-stroke motor aphasia: A Bayesian network meta-analysis - Feng, Sisi; Tang, Mingzhi; Huang, Gan; Wang, Jumei; Lv, Yulan; He, Sijin; Liu, Duo; Gu, Lihua (Frontiers in Neurology, 2022)
Background Motor aphasia, which can affect the communication ability of patients and even triggers severe psychological disorders, is one of the most common sequelae after stroke. Acupuncture (a typical complementary alternative therapy) is frequently combined with speech training (ST) to treat post-stroke motor aphasia (PSMA) and presents significant efficacy. However, the most effective acupuncture intervention is still unknown. This study aims to analyze the efficacy of several acupuncture approaches combined with ST for PSMA to identify the best intervention for clinical decision-making by using network meta-analysis (NMA). Methods Eight major databases were searched from the time of their establishment to March 2022. Clinical efficacy rate (CER) was used as the primary outcome indicator. R software (version 4.13.0) and STATA software (version 16.0) were used to analyze the data. Results A total of 29 randomized controlled trials (RCTs) and six treatment regimens were included in this study. In the pair-wise meta-analysis, we found that the efficacy of scalp-tongue acupuncture (STA) combined with ST [OR = 8.30; 95% Credible interval (CrI): 3.87, 17.33], tongue acupuncture (TA) combined with ST (OR = 3.95; 95% CrI: 2.27, 6.89), scalp-body acupuncture (SBA) combined with ST (OR = 3.75; 95% CrI: 2.26, 6.22), scalp acupuncture (SA) combined with ST (OR = 2.95; 95% CrI: 1.74, 5.0), and body acupuncture (BA) combined with ST (OR = 2.30; 95% CrI: 1.26, 4.19) were significantly superior to that of ST. In addition, the efficacy of STA + ST was significantly superior to that of SA +ST (OR = 2. 82; 95% CrI: 1.24, 6.38) and BA + ST (OR = 3.61; 95% CrI: 1.40, 9.29). According to the surface under the cumulative ranking curve (SUCRA), STA + ST (SUCRA = 97.9%) may be the best treatment regimen to improve the clinical outcome in patients with PSMA. Conclusion The NMA showed that STA combined with ST may be the best treatment to improve CER, compared with other combination treatments. However, since the overall quality and number of studies are limited, further RCTs with a large sample and multicenter are needed for further validation. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=316081, identifier CRD42022316081.